Poverty alleviation and microfinance for the economy of Pakistan: A case study of Khushhali Bank in Sargodha - Stylianou Tasos; Muhammad Ijaz Amjad; Masood Sarwar Awan; Muhammad Waqas (Economies, 2020)
Poverty is a universal reality, and no one can deny the omnipresence of it all over the world. It is considered as the most harmful economic and social problem of human beings since their creation. It affects individuals as well as society as a whole in a very destructive way, and it is considered that poverty is the mother of all human rights violations. Perhaps no one would argue against the notion that microfinance can be a very useful apparatus in human, social, economic, political and national development. Microfinance has been established to fill the gap of a missing credit market for the poor. Among all other anti-poverty strategies, it has become one of the most important and successful tools for poverty elimination throughout the world. In this study, we investigate the impact of microfinance on poverty alleviation for the economy of Pakistan. The literacy is very poor for the area of Pakistan, so our research will help policy makers in making the right decisions in order to help the people that are living below the poverty line. Primary data of 300 households from Khushhali Microfinance Bank Limited were collected. The findings reveal that microfinance imparts a vital role in poverty eradication where the poverty level has decreased from 42.67% in comparison household (CHH) to 29.33% in the program household (PHH). Finally, it unveils the fact that there is a negative association between the provision of microfinance and poverty level of the household. The availability of micro financing facilities to the poor has declined the poverty rate from 42.67 percent to 29.33 percent. The Logistic Regression model implies that poverty has a negative association with the duration of microfinance, education and existence of a market in the locality, whereas it is positively related to family size and gender of the respondent.
Keywords: F41; E60; I38; 330; macroeconomics; poverty; microfinance; Pakistan